Arginine-, D-arginine-vasopressin, and their inverso analogues in micellar and liposomic models of cell membrane: CD, NMR, and molecular dynamics studies - Lubecka, Emilia A; Sikorska, Emilia; Sobolewski, Dariusz; Prahl, Adam; Slaninová, Jiřina; Ciarkowski, Jerzy (European biophysics journal, 2015)
We describe the synthesis, pharmacological properties, and structures of antidiuretic agonists, arginine vasopressin (AVP) and [D-Arg(8)]-vasopressin (DAVP), and their inverso analogues. The structures of the peptides are studied based on micellar and liposomic models of cell membranes using CD spectroscopy. Additionally, three-dimensional structures in mixed anionic-zwitterionic micelles are obtained using NMR spectroscopy and molecular dynamics simulations. NMR data have shown that AVP and DAVP tend to adopt typical of vasopressin-like peptides β-turns: in the 2-5 and 3-6 fragments. The inverso-analogues also adopt β-turns in the 3-6 fragments. For this reason, their inactivity seems to be due to the difference in side chains orientations of Tyr(2), Phe(3), and Arg(8), important for interactions with the receptors. Again, the potent antidiuretic activity of DAVP can be explained by CD data suggesting differences in mutual arrangement of the aromatic side chains of Tyr(2) and Phe(3) in this peptide in liposomes rather than of native AVP. In the presence of liposomes, the smallest conformational changes of the peptides are noticed with DPPC and the largest with DPPG liposomes. This suggests that electrostatic interactions are crucial for the peptide-membrane interactions. We obtained similar, probably active, conformations of the antidiuretic agonists in the mixed DPC/SDS micelles (5:1) and in the mixed DPPC/DPPG (7:3) liposomes. Thus it can be speculated that the anionic-zwitterionic liposomes as well as the anionic-zwitterionic micelles, mimicking the eukaryotic cell membrane environment, partially restrict conformational freedom of the peptides and probably induce conformations resembling those of biologically relevant ones.
Keywords: buněčná membrána; micely; antidiuretika; Molecular Sequence Data; Protein Binding; molekulární sekvence - údaje; Liposomes; krysa rodu Rattus; Inverso analogues; Micelles; zvířata; arginin vasopresin; peptidy; potkani Wistar; Peptides; simulace molekulární dynamiky; Amino Acid Sequence; Rats, Wistar; Molecular Dynamics Simulation; liposomy; vazba proteinů; Anionic–zwitterionic micelles; Rats; Animals; Cell Membrane; Antidiuretic Agents; terciární struktura proteinů; Protein Structure, Tertiary; Antidiuretic agonists; Arginine Vasopressin; sekvence aminokyselin